Patients' view on non-surgical and surgical periodontal therapy in relation to oral health: A narrative review - Nurul Qamar Salehuddin; Budi Aslinie Md Sabri; Farha Ariffin (Elsevier, 2022)
The ideal goal of periodontal treatment is to eliminate inflammation in deep pocket depths and prevent further disease progression. Various treatment modalities including non-surgical and surgical treatment throughout the active phase of therapy are typically applied to achieve these goals. Currently, evidence showed that periodontal surgery may yield superior results on a short-term level, however in a long-term period both treatments are comparable. This can be interpreted that other factors besides clinical factors would determine the mode of treatment to be chosen. The impact of periodontal treatment on patients' Oral-health-related-Quality-of-Life (OHQoL) plays a significant contributing factor in managing periodontitis. Besides OHQoL, economic evaluation by cost-effectiveness (CEA) and cost-utility analysis (CUA) has been increasingly established as an important aspect of decision-making in periodontal therapy. Cost-effective treatment is where one treatment benefits exceed the cost. Generally, the benefits of dental treatment comprises of improved or retained functionality and aesthetics and achieve patients' satisfaction by elimination of discomforts due to the disease. Thus, the aim of this article is to provide a comprehensive overview of different modalities of therapy to control periodontitis, discussing the direct effect of varying methods of treatment on patients' OHQoL and the economic evaluation of periodontal therapy.